2004
DOI: 10.1016/j.ejcts.2004.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of obesity on in-hospital and early mortality and morbidity after myocardial revascularization

Abstract: Objective: Obese patients are thought to have an increased risk for complications in coronary artery bypass surgery. Several risk stratification systems do not identify obesity as a variable for risk adjustment. The aim of this study is to evaluate the in-hospital and early (one year) mortality and morbidity in obese and non-obese patients after a CABG in the UMC St Radboud. Methods: The data of 1130 patients undergoing a myocardial revascularization from January 2000 to August 2002 were analyzed. Obesity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 21 publications
1
27
1
3
Order By: Relevance
“…Some studies found a higher incidence of mortality in the postoperative and mid-term follow-up after CABG in obese patients, 14-17 whereas others did not find this association. [20][21][22][23][24][25][26][27][28][29][30][31] There are reports of increased operative mortality in morbidly obese individuals. 18, 19 In a recent systematic review, Oreopoulos et al reported a lower mortality in obese patients undergoing CABG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found a higher incidence of mortality in the postoperative and mid-term follow-up after CABG in obese patients, 14-17 whereas others did not find this association. [20][21][22][23][24][25][26][27][28][29][30][31] There are reports of increased operative mortality in morbidly obese individuals. 18, 19 In a recent systematic review, Oreopoulos et al reported a lower mortality in obese patients undergoing CABG.…”
Section: Discussionmentioning
confidence: 99%
“…13 Although some authors have reported higher postoperative and mid-term mortality in obese 14-17 and morbidly obese 18, 19 patients after CABG, others have failed to confirm this association. [20][21][22][23][24][25][26][27][28][29][30][31] Obesity is considered as a predictor for post-cardiac surgery 30-day mortality in a risk stratification system devised by Parsonnet et al 10 Although several studies have demonstrated an increased cardiovascular risk in obese individuals, there is an increasing body of literature describing the obesity paradox, suggesting possible protection from adverse cardiovascular events in obese patients, including congestive heart failure (CHF). 6,32-37 Some of these studies also suffer Outcome After Isolated CABG in Obese Individuals from selection bias since obese patients, on average, have a higher number of associated comorbidities, and the use of logistic regression analysis may not completely adjust for this selection bias.…”
mentioning
confidence: 99%
“…In patients undergoing coronary by-pass surgery, those with low BMI were at higher risk for adverse outcome, compared to obese patients [10]. In another study, obesity was not associated with increased in-hospital or 1-year mortality following coronary by-pass surgery [16]. In yet another study of patients after coronary by-pass surgery, those who were overweight or obese had significantly better survival free from major cardiac or cerebrovascular events, compared to those with normal BMI [15].…”
Section: Discussionmentioning
confidence: 95%
“…The results from prior studies on the prognostic importance of BMI in patients with established coronary artery disease and after acute myocardial infarction are inconsistent [3][4][5][6][7][8][9][10][11][12][13][14][15][16]19]. In a study in survivors of a first acute myocardial infarction, obesity was associated with increased risk of recurrent coronary events during 3 years of follow-up [3].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation